The Influence of NPL, BOPO, and LDR on ROA on Local Government Banks Registered In OJK in 2018-2020. - Shilvi Maljeti; Gusganda Suria Mandala (YUME : Journal of Management, 2022)
This research was conducted with the aim of analyzing how the influence of Non Performing Loan (NPL), BOPO, and Loan to Deposit Ratio (LDR) will Return On Asse (ROA) through the quarterly financial ratio report  on local government banks in the period March 2018 to December 2020.  taken from data published by the Financial Services Authority (OJK).This research is a study conducted with quantitative research methods using secondary data, taken from financial statements, especially financial ratio statements published on the official OJK website.The tools used in analyzing the data in this study are SPSS 26 and Microsoft Excel using multiple linear regression data analysis methods, with this method shown how the influence occurs between independent variables and variable dependents.The results of this study showed that simultaneously NPL, BOPO and LDR had an influence on ROA in Local Government Banks which was studied by 74% and 26% others were influences caused by other factors that did not fall into the variables studied in this study. While partial test results showed that NPL had a positive and insignificant effect on ROA, BOPO had a significant negative effect on ROA and LDR had  no significant positive effect on ROA.